2014
DOI: 10.1021/ie501160h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Solar-Photocatalytic Degradation of Combined Chlorophenols Using Ferric Ions and Hydrogen Peroxide

Abstract: The influences of ferric ions (Fe3+) and hydrogen peroxide (H2O2) on the degradation of combined chlorophenols during solar/TiO2 process were investigated. 4-Chlorophenol (4-CP) and 2,4-dichlorophenol (2,4-DCP) were used as a chlorophenols combined mixture. Fe3+ ions have shown considerable effect on the solar-photocatalytic degradation rate of the mixture and its intermediates. Different amounts of Fe3+ ions were used, and the optimum value was 10 mg/L. At these conditions, three major intermediates were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…It was found that the ability of 2.0 wt.% Ag@Mg 4 Ta 2 O 9 for atrazine degradation was retained and it can be reused many times with the similar efficiency. Abeish et al (2014) investigated influence of ferric ions and hydrogen peroxide on the degradation of combined chlorophenols in solar/TiO 2 process. The 4-chlorophenol (4-CP) and 2,4-dichlorophenol (2,4-DCP) were used as model pollutants chlorophenols.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the ability of 2.0 wt.% Ag@Mg 4 Ta 2 O 9 for atrazine degradation was retained and it can be reused many times with the similar efficiency. Abeish et al (2014) investigated influence of ferric ions and hydrogen peroxide on the degradation of combined chlorophenols in solar/TiO 2 process. The 4-chlorophenol (4-CP) and 2,4-dichlorophenol (2,4-DCP) were used as model pollutants chlorophenols.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophenols (CPs) are significant chemical intermediates for the manufacture of fungicides, antiseptics, dyes, pesticides, and personal-care-products in various industries [1][2][3][4]. The high toxicity and poor biodegradability of CPs has classified them in the blacklist of priority pollutants announced by European regulatory authorities and the US Environmental Protection Agency [5][6][7]. The residues of these chemicals are exposed to the air, water, and soil from industrial wastewater emission due to their global manufacture and purchase, and often have toxicological effects on human beings, such as skin and mucosa irritability, soft tissue sarcomas, and exposure via the contamination of groundwater and soil [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Chlorinated phenolic compounds i.e. 2-chlorophenol (2CP), 4-chlorophenol (4-CP), 2,4dichlorophenol (2,4-DCP) and pentachlorophenol (PCP) have been widely known to have severe detrimental effects on aquatic ecosystem and human health [1]. In the chlorinated phenolic families, 2CP due to high toxicity, carcinogenic character, persistence in the environment, and low biodegradability have been listed among priority pollutants by the United States Environmental Protection Agency [2].…”
Section: Introductionmentioning
confidence: 99%